1986
DOI: 10.1136/gut.27.9.1035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pancreas necrosis in severe acute pancreatitis: imaging procedures versus clinical staging.

Abstract: SUMMARY One hundred and five of 395 patients with acute pancreatitis were surgically treated in our clinic from 1981 to 1984. Ninety three of these patients were examined with contrast enhanced computed tomography and/or ultrasound and were clinically assessed according to Ranson's objective criteria before operation. At operation, 77 patients showed necrotising pancreatitis and 16 showed biliary acute interstitial pancreatitis. Ninety per cent of the cases with extensive and 79% of those with minor necroses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
7

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(62 citation statements)
references
References 16 publications
1
54
0
7
Order By: Relevance
“…Indeed, the risks of acute pancreatitis are most of all infectious complications that are directly linked to the presence of necrosis, a favourable environment to the development of bacteria [3,7,[19][20][21][22][23][24][25][26][27][28]. The overall risk of infection does not exceed 10%, but in case of necrosis, it reaches 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the risks of acute pancreatitis are most of all infectious complications that are directly linked to the presence of necrosis, a favourable environment to the development of bacteria [3,7,[19][20][21][22][23][24][25][26][27][28]. The overall risk of infection does not exceed 10%, but in case of necrosis, it reaches 70%.…”
Section: Discussionmentioning
confidence: 99%
“…A CT is the most frequently used radiological investigation to evaluate AP and detect necrosis. Intravenous contrast-enhanced CT distinguishes pancreatic necrosis with an accuracy of 90% (11). Several CT scoring systems have been reported as being better than other systems for predicting the severity of AP.…”
Section: Discussionmentioning
confidence: 99%
“…The CRP test is widely available in laboratories, and various researchers have suggesting using CRP as a prognostic marker for severe AP (9). However, a primary problem is the lack of specificity to predict severe AP at a level not greater than 80% (2,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…29 While Block S, Maier W et al reported pancreatic necrosis in 90% of cases in acute severe pancreatitis and 79% of the cases of mild pancreatitis which was dissimilar to present study. 30 In chronic pancreatitis, pancreatic calcification and visualization of pancreas are seen in 100% of cases. Followed by pancreatic enlargement in 60% of cases and pseudocyst in 30% of cases.…”
mentioning
confidence: 99%